Protective equipment applicable to a centralized cytostatic preparation unit - Gonçalves, Ana (2022)
Occupational exposure to cytotoxic agents has been recognized as a potential danger to the health of handlers. However, collective and individual protection equipment has been developed for use by professionals. This article aims to identify and describe the protection equipment applicable to a centralized unit of cytostatics preparation, using a qualitative and quantitative descriptive analysis. A questionnaire survey yielded 83 responses, covering 18 centralized cytostatic preparation units. The results show some weaknesses detected in some institutions such as the absence of a shower and eyewash fountain, the lack of knowledge about the procedures manual, and the use of a surgical mask. However, the results point to awareness by the general manipulators regarding the use of some personal protective equipment. This study contributes to the investigation of the use of equipment for the protection of cytostatic manipulators at work in centralized cytostatic preparation units.